2018
DOI: 10.1111/1460-6984.12365
|View full text |Cite
|
Sign up to set email alerts
|

Cognate effects and cognitive control in patients with parallel and differential bilingual aphasia

Abstract: The present data indicate preserved language co-activation for patients with parallel as well as differential aphasia. Furthermore, the results suggest a general cognitive control dysfunction, specifically for differential aphasia. Taken together, the results of the current study provide further support for the hypothesis of impaired cognitive control abilities in patients with differential aphasia, which has both theoretical and practical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Four of the studies that did not find abnormal interference nevertheless found bPWA to be significantly slower and/or less accurate overall on tasks (Calabria et al, 2019; Gray & Kiran, 2016, 2019; Van der Linden et al, 2018b). 1 This shows that while the specific ability to resist interference from distractors may be intact, other cognitive abilities necessary to perform the task, such as processing speed or sustained attention, may be below normal performance.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Four of the studies that did not find abnormal interference nevertheless found bPWA to be significantly slower and/or less accurate overall on tasks (Calabria et al, 2019; Gray & Kiran, 2016, 2019; Van der Linden et al, 2018b). 1 This shows that while the specific ability to resist interference from distractors may be intact, other cognitive abilities necessary to perform the task, such as processing speed or sustained attention, may be below normal performance.…”
Section: Resultsmentioning
confidence: 98%
“…Evidence for a more direct relationship between EC deficits and selective recovery of one language is provided by Verreyt et al (2013) and corroborated by the group comparison of Van der Linden et al (2018b). They investigated bPWA's language control and EC abilities and found that bPWA with differential recovery of their languages tentatively showed more difficulties with both linguistic control and inhibitory control, compared to bPWA with parallel recovery.…”
Section: Domain Generality: Evidence From Functional Communicationmentioning
confidence: 85%
See 3 more Smart Citations